Concise, Stereocontrolled Synthesis of the Citrinadin B Core Architecture - Guerrero, Carlos A. (2011)
[Image: see text] A concise, stereocontrolled synthesis of the citrinadin B core architecture from scalemic, readily available starting materials is disclosed. Highlights include ready access to both cyclic tryptophan tautomer and TRANS-2,6-disubstituted piperidine fragments, an efficient, stereoretentive mixed Claisen acylation for the coupling of these halves, and further diastereoselective carbonyl addition and oxidative rearrangement for assembly of the core.